Two-period model of Bank lending channel: Basel II regulatory constraints - Fathin Faizah Said (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper predicts the dynamic model of the bank lending channel under Basel II regulatory constraints with monopolistic competition. The two-period model is chosen in order to demonstrate the effects of new Basel capital constraints on the risks of banks assets during both periods; and the amount of equity in the second period. The prediction of period one and two are shown to have the same effect and the only difference is the constraint. The regulatory constraint in periods one and two are predicted depending on the regulatory parameters and constraints for both periods. Thus, the effect of optimal rates on a policy rate is felt greater or less during the first period than during the second period, which means tightening capital requirements increases or decreases the risks of assets and banks taking higher or lower risks, respectively,during the first period than during the second period.